The effects of caffeine, taurine, or caffeine-taurine coingestion on repeat-sprint cycling performance and physiological responses - Warnock,R.; Jeffries, O.; Patterson, S.; Waldron, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To investigate the effects of caffeine (C), taurine (T), caffeine and taurine coingestion (C +T), or placebo (P) on repeated Wingate cycling performance and associated physiological responses. Methods: Seven male team-sport players participated in a randomized, single-blind, crossover study, where they completed 3 Wingate tests, each separated by 2 min, an hour after ingesting: C (5 mg/kg body mass [BM]), T (50 mg/kg BM), C +T (5 mg/kg BM+50 mg/kg BM), or P (5 mg/kg BM) in a gelatin capsule. Performance was measured on an ergometer, and blood lactate, perceived exertion, heart rate (HR), mean arterial pressure (MAP), and rate pressure product (RPP) were measured at rest (presupplement), baseline (1h postsupplement), and during and after exercise. Results: Magnitude-based inferences revealed that all of the supplements increased (small to moderate, likely to very likely) mean peak power (MPP), peak power (PP), and mean power (MP) compared to P, with greater MPP, PP, and MP in T compared to C (small, possible). Intrasprint fatigue index (%FIIntra) was greater in T compared to P and C (moderate, likely), and %FIInter was lower in T compared to C (small, possible). C and C +T increased HR, MAP, and RPP compared to P and T at baseline (moderate to very large, likely to most likely); however, these only remained higher in C compared to all conditions in the final sprint. Conclusions: T elicited greater improvements in performance compared to P, C, or C +T while reducing the typical chronotropic and pressor effects of C.